2015
DOI: 10.1089/vim.2014.0150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Foot-and-Mouth Disease Virus O/CHN/Mya98/33-P Strain Leader Protein on Viral Replication and Host Innate Immunity

Abstract: Foot-and-mouth disease virus (FMDV) O/CHN/Mya98/33-P strain was isolated from the esophageal-pharyngeal fluid sample of cattle, and was shown to cause persistent infection. Its leader protein contains 200 amino acids with one amino acid deletion, which is upstream and next to the second initiation codon compared with the majority of FMDV Mya98 strains. The FMDV genome includes two initiation codons that can produce two different leader proteins, Lab (from the first AUG) and Lb (from the second AUG). For conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Workers have created modified viruses by mutating deleterious genes, altering replication fidelity, and deoptimizing codons, and these demonstrated protection in animals with variable degrees of success [60]. Modification in the leader protein of FMDV or by changing one of the two translation initiation sites in the virus has been demonstrated, though studies in animals are limited [56,60,61,62,63,64]. It was demonstrated that RNAs carrying the deletion of the stem loop in the 3′ UTR on a serotype-O FMDV genome were innocuous when inoculated in pigs but elicited specific humoral and cellular immune responses [65].…”
Section: Trends and Advances In Vaccines Against Fmdvmentioning
confidence: 99%
“…Workers have created modified viruses by mutating deleterious genes, altering replication fidelity, and deoptimizing codons, and these demonstrated protection in animals with variable degrees of success [60]. Modification in the leader protein of FMDV or by changing one of the two translation initiation sites in the virus has been demonstrated, though studies in animals are limited [56,60,61,62,63,64]. It was demonstrated that RNAs carrying the deletion of the stem loop in the 3′ UTR on a serotype-O FMDV genome were innocuous when inoculated in pigs but elicited specific humoral and cellular immune responses [65].…”
Section: Trends and Advances In Vaccines Against Fmdvmentioning
confidence: 99%
“…Extraneous cofactors also contribute to RGD attachment, e.g., both FMDV attachment to cells and integrin receptor activity are dependent on divalent cations [40], and there is evidence that disialogangliosides contribute to the attachment of melanoma cells to RGD-containing substrates [28]. Amino acids of the VP2 region (1-33) are also capable of producing antibody response elicited by the VP1 region, but it is weakly immunogenic because the N-terminus of the VP2 protein is positioned at the bottom of the three-fold symmetry axis of the virus protein coat [43].…”
Section: Insights Into Genetic/molecular Dynamics Of Fmdmentioning
confidence: 99%